Measurement of the production performance through the comparison between the budgeted and the actually achieved time: a Case Study (ADMPG Journal, 2019)
This article aims to present a statistical study utilized for the verification and performance measurement regarding the used labor time for the achievement of the metallurgic production process in an industry of this segment, located in Castro, Paraná State. The work demonstrates a comparative study between the budgeted and the actually achieved time, presenting as well, the advantages and objectives that can be realized through the performance and productivity measurement. According to the results, the possibility of improvement in processing time could be verified, reducing the hand labor costs and increasing the competitiveness of the company.